2023
DOI: 10.3390/min13091186
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of Rare Earth Elements: Perspectives from Mineral Characteristics and Microbial Species

Shulan Shi,
Jinhe Pan,
Bin Dong
et al.

Abstract: Bioleaching exhibits high potential for the processing of low-grade complex mineral resources. With the development of the economy and an increase in demand, rare earth elements (REEs) in secondary resources, such as phosphogypsum, red mud and coal-related resources, are gaining more and more attention. In this review, the bioleaching performance of diverse microorganisms is summarized and compared for primary (mainly monazite) and secondary REE resources, based on publications from the past decade. The minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…REEs occur in various forms as phosphates, sulphates, or silicates in these primary resources. Secondary REE resources typically comprise wastes like phosphogypsum, red mud, coal-related resources, and WEEE (Fathollahzadeh et al 2019 ; Shi et al 2023 ). Traditional extraction methods often involve the use of harsh chemicals and can have significant environmental impacts.…”
Section: Bio-recovery Of Reesmentioning
confidence: 99%
“…REEs occur in various forms as phosphates, sulphates, or silicates in these primary resources. Secondary REE resources typically comprise wastes like phosphogypsum, red mud, coal-related resources, and WEEE (Fathollahzadeh et al 2019 ; Shi et al 2023 ). Traditional extraction methods often involve the use of harsh chemicals and can have significant environmental impacts.…”
Section: Bio-recovery Of Reesmentioning
confidence: 99%
“…At an even lower pH of pH 1.0-3.0, the formation of sulfuric acid allows the solubilization of metals. It has been found that low pH does not negatively affect the growth and metabolism of A. thiooxidans and A. ferrooxidans [26][27][28]. The cultivation of bioleaching bacteria was carried out at a temperature of 20 • C. The optimal temperature for the growth of acidic bacteria A. thiooxidans and A. ferrooxidans is 30 • C [26][27][28].…”
Section: Materials and Reagents Used In Stage II Researchmentioning
confidence: 99%
“…It has been found that low pH does not negatively affect the growth and metabolism of A. thiooxidans and A. ferrooxidans [26][27][28]. The cultivation of bioleaching bacteria was carried out at a temperature of 20 • C. The optimal temperature for the growth of acidic bacteria A. thiooxidans and A. ferrooxidans is 30 • C [26][27][28]. Lowering the culture temperature resulted from the assumption of reducing energy demand (thermal energy) during the cultivation of bioleaching bacteria.…”
Section: Materials and Reagents Used In Stage II Researchmentioning
confidence: 99%
“…The advantages of processing waste from the existing mine tailings are availability and large amounts of input materials. However, as the defined waste raw materials are often characterised by lower concentrations of metals, it is essential to choose suitable processing procedures for the mentioned materials to achieve high yields of metals and to meet the environmental and economic aspects of the process for the subsequent introduction of the technology into operational conditions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%